
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.


\(a,-5x\left(x-3\right)\left(2x+4\right)-\left(x+3\right)\left(x-3\right)+\left(5x-2\right)\left(3x+4\right)\)
\(=-5x\left(2x^2-x-12\right)-\left(x^2-9\right)+15x^2+20x-6x-8\)
\(=-10x^3+5x^2+60x-x^2+9+15x^2+20x-6x-8\)
\(=-10x^3+19x^2+74x+1\)
\(b,\left(4x-1\right)x\left(3x+1\right)-5x^2.x\left(x-3\right)-\left(x-4\right)x\left(x-5\right)\)\(-7\left(x^3-2x^2+x-1\right)\)
\(=\left(4x^2-x\right)\left(3x+1\right)-5x^4-15x^3-\left(x^2-4x\right)\left(x-5\right)\)\(-7x^3+14x^2-7x+7\)
\(=12x^3+x^2-x-5x^4-15x^3-x^3+9x^2+20x\)\(-7x^3+14x^2-7x+7\)
\(=-5x^4-11x^3+24x^2+12x+7\)
\(c,\left(5x-7\right)\left(x-9\right)-\left(3-x\right)\left(2-5x\right)-2x\left(x-4\right)\)
\(=5x^2-52x+63-6+17x-5x^2-2x^2+8x\)
\(=-2x^2-27x+57\)
\(d,\left(5x-4\right)\left(x+5\right)-\left(x+1\right)\left(x^2-6\right)-5x+19\)
\(=5x^2+21x-20-x^3-x^2+6x+6-5x+19\)
\(=-x^3+4x^2+22x+5\)
\(e,\left(9x^2-5\right)\left(x-3\right)-3x^2\left(3x+9\right)-\left(x-5\right)\left(x+4\right)-9x^3\)
\(=9x^3-27x^2-5x+15-9x^3-27x^2-x^2+x+20-9x^3\)
\(=-9x^3-55x^2+4x+35\)
\(g,\left(x-1\right)^2-\left(x+2\right)^2\)
\(=x^2-2x+1-x^2-4x-4\)
\(=-6x-3\)


a)\(x^4+6x^3+11x^2+6x+1\)
\(=x^4+9x^2+1+6x^3+6x+2x^2\)
\(=\left(x^2+3x+1\right)^2\)

ta có
a. (5x-7)(x-9)-(-x+3)(-5x+2)= 2x(x-4)-(x-1)(2x+3)
\(\Leftrightarrow5x^2-52x+63-\left(5x^2-17x+6\right)=2x^2-8x-\left(2x^2+x-3\right)\)
\(\Leftrightarrow-35x+57=-9x+3\Leftrightarrow26x=54\Leftrightarrow x=\frac{27}{13}\)
b. (x-3)(-x+10)+(x-8)(x+3)= (5x^2-1)(x+3)-5x^3-15x^2
\(\Leftrightarrow-x^2+13x-30+x^2-5x-24=5x^3+15x^2-x-3-5x^3-15x^2\)
\(\Leftrightarrow8x-54=-x-3\Leftrightarrow9x=51\Leftrightarrow x=\frac{17}{3}\)

a: \(\Leftrightarrow5x^2-45x-7x+63-\left(5x-2\right)\left(x-3\right)=2x^2-8x-2x^2-3x+2x+3\)
\(\Leftrightarrow5x^2-52x+63-\left(5x-2\right)\left(x-3\right)=-9x+3\)
\(\Leftrightarrow5x^2-52x+63-5x^2+15x+2x-6=-9x+3\)
=>-37x+57=-9x+3
=>28x=-54
hay x=-27/14
b: \(\Leftrightarrow-x^2+19x+3x-30+x^2-5x-24=\left(5x^2-1\right)\left(x+3\right)-5x^3-15x^2\)
\(\Leftrightarrow17x-54=5x^3+15x^2-x-3-5x^3-15x^2\)
=>18x=51
hay x=17/6

Bài 2: Tính giá trị của biểu thức sau:
\(16x^2-y^2=\left(4x+y\right)\left(4x-y\right)\)
Thay \(\hept{\begin{cases}x=87\\y=13\end{cases}}\)
\(\Rightarrow\left(4.87+13\right)\left(4.87-13\right)=361.335=120935\)
Bài 4: Tìm x
a) \(9x^2+x=0\)
\(\Rightarrow x\left(9x+1\right)=0\)
\(\Rightarrow\orbr{\begin{cases}x=0\\9x+1=0\end{cases}}\Rightarrow\orbr{\begin{cases}x=0\\x=\frac{-1}{9}\end{cases}}\)
b) \(27x^3+x=0\)
\(\Rightarrow x\left(27x^2+1=0\right)\)
\(\Rightarrow\orbr{\begin{cases}x=0\\27x^2+1=0\end{cases}}\Rightarrow\orbr{\begin{cases}x=0\\27x^2=\left(-1\right)\end{cases}}\Rightarrow\orbr{\begin{cases}x=0\\x^2=\frac{-1}{27}\end{cases}}\)
Ta có: \(\frac{-1}{27}\) loại vì \(x^2\ge0\forall x\)
Vậy \(x=0\)
(5x+1)(x+3)-(x-2)(5x-4)
=5x2+15x+x+3-(5x2-4x-10x+8)
=5x2+15x+x+3-5x2+4x+10x-8
=30x-5
(x^2+x-3)(x^2-x+3)
=[x2+(x-3)][x2-(x-3)]
=x2-(x-3)2
=x2-(x2-6x+9)
=x2-x2+6x-9
=6x-9